Mulberry leaf reduces inflammation and insulin resistance in type 2 diabetic mice by TLRs and insulin Signalling pathway - Simin Tian; Min Wang; Chenyue Liu; Hongbin Zhao; Baosheng Zhao (BMC, 2019)
Abstract Background It has been testified that Diabetes mellitus (DM) has a close association with chronic inflammation and Toll-like Receptors (TLRs), and DM could be prevented by mulberry leaf. Therefore, a hypothesis came into being that mulberry leaf could ameliorate proinflammation and insulin resistance (IR) through TLRs and insulin signalling pathways. Methods Water extracts of mulberry leaf (WEM) was given to diabetic mice by gavage for 10 weeks, and the diabetic mice was injected with low-dose streptozocin, fed with high-fat and high-sugar diet. Oral glucose tolerance tests (OGTTs) were conducted. At the same time, homeostasis model assessment of insulin (HOMA-IR) and the level of the inflammatory factor, tumour necrosis factor-α (TNF-α) was measured. The expressions of critical nodes of TLRs and insulin signalling pathway were also examined. Results WEM contributed to a significant decrease in fasting blood glucose, AUC from the investigation of OGTTs and HOMA-IR. The levels of the inflammatory factor, tumour necrosis factor-α (TNF-α) also declined. Moreover, WEM suppressed the expression of TLR2, myeloid differentiation primary-response protein 88 (MyD88), tumour-necrosis-factor receptor-associated factor 6 (TRAF6), nuclear factor kappa B (NF-κB) in the skeletal muscle. WEM could up-regulate the expression of insulin receptor (InsR) and insulin receptor substrate 1 (IRS1), and down-regulate the phosphorylation of IRS1 in adipose tissue. Conclusion Through this study, a conclusion could be made that WEM mitigates hyperglycemia, IR, and inflammation through the interactions among TLR2 signalling pathway, insulin signalling pathway and TNF-α.